The Confrontation Between Quakers and Clergy 1652-1656: Theology and Practice - Johnston, Margaret Anne (Quaker studies, 2021)
The conflict between the clergy and the earliest Quakers can be better understood in the context of the "mainstream" Puritan tradition. Analysis of the pamphlets interchanged is used to investigate what the participants in the confrontation were hoping to achieve, what background they were were drawing on and what theological issues arose. Analysis of the pamphlets interchanged shows that the Quakers gave priority to the abolition of the paid professional ministry, while the clergy argued that the Quaker movement should be suppressed. The Quakers claimed to be guided by the inward light of Christ, but they supported their arguments with biblical references. Neither group were willing to admit to a source for their methods of biblical interpretation, but the clergy were clearly drawing on the patristic tradition, to which Jean Calvin and William Perkins were indebted; the Quakers may have learned from earlier radical groups. Each group used theological arguments to support very different codes of conduct. The clergy claimed to be entitled to the support of the magistracy in suppressing Quakers, but in the confused circumstances of the Interregnum the extent to which such support was forthcoming varied from place to place. This article focuses on different approaches to practice arising from these theological differences.